Escherichia coli in the T11-12 Thoracic Vertebrae: A Case Report - Weng D; Zhou H; Huang G; Cao Q; Wang H; Cao Z; Xie Q (Infection and Drug Resistance)
Dandan Weng,1,* Hongyuan Zhou,1,* Guancheng Huang,1 Qingren Cao,2 Huafeng Wang,3 Zhujun Cao,2 Qing Xie2 1Department of Infectious Diseases, Yuyao People’s Hospital, Ningbo, Zhejiang, People’s Republic of China; 2Department of Infectious Diseases, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Department of Pathology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Xie; Zhujun Cao, Department of Infectious Diseases, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, 197 Ruijin Er Road, Shanghai, 200025, People’s Republic of China, Email xieqingrjh@163.com; estherlucifer@163.comBackground: Pyogenic thoracic spondylitis is a rare but severe infection, particularly when complicated by sepsis and acute kidney injury (AKI). Early diagnosis and precise management are essential for improving outcomes, given the limitations of traditional microbiology detection methods in identifying the causative pathogens.Case Presentation: A 68-year-old immunocompetent male presented with recurrent fever, fatigue, loss of appetite and initial evidence of sepsis and AKI upon admission. With the prompt computed tomography (CT)-guided percutaneous biopsy of the thoracic vertebrae, Escherichia coli was identified as the causative pathogen using metagenomic next-generation sequencing (mNGS). A diagnosis of pyogenic thoracic spondylitis was then made followed by the treatment of antibiotics optimized by therapeutic drug monitoring (TDM) techniques. With a total effective antibiotic treatment period of 7 weeks, the patient recovered without resorting to surgical interventions.Conclusion: This is a rare case of acute thoracic spondylitis caused by E. coli, successfully treated without surgery. This case highlights the significant challenges in diagnosis and treatment. It underscores the value of mNGS in identifying rare infections and emphasizes the role of TDM in optimizing antibiotic therapy, providing a reference for future cases of rare and critical infections with fever of unknown origin.Keywords: pyogenic thoracic spondylitis, metagenomic next-generation sequencing, mNGS, therapeutic drug monitoring, TDM, antibiotic therapy, fever of unknown origin